The adverse reactions to antitubercular and antirretrovirales medicines in adult patients reported to the Clinical educational hospital surgical Daniel Alcides Carrión period 2012-2013. - Andamayo Flores, Diana Esmeralda (2020)
OBJECTIVE: To determine the adverse reactions to antitubercular and antirretrovirales medicines in adult patients reported to the Clinical Educational Hospital surgical Daniel Alcides Carrión. METHOD: Corresponds to a observacional, retrospec- tive investigation, applied, of explanatory descriptive level and causal design, made in 49 reports of suspi- cion notification of RAMs to medicines of adult pa- tients who consumed antitubercular medicines, antirretrovirales that frequent the Clinical Educational Hospital Surgical Daniel Alcides Carrión. RESULTS: As far as the prevalence of the adverse re- actions to antitubercular medicines, can be observed that the Rifampicina was the one that simultaneously caused multiple adverse reactions like gastritis, nauseas and vomits; whereas with the Antirretrovirales medicines the Zidovudina was the one that produced severe anemia frequently, moderate anemia and neutropenia.CONCLUSIONS: In this study the Rifampicina caused greater effects at level of the gastrointestinal system like nauseas, and vomits, and of moderate type according to degree toxicity, however with antirretrovirales medicines the Zidovudina produced severe anemia, moderate anemia and neutropenia being the most aggressive medicine in comparison to the others, and of toxicity of serious degree.